2008
DOI: 10.3390/molecules14010068
|View full text |Cite
|
Sign up to set email alerts
|

Enaminones as Building Blocks in Heterocyclic Syntheses: Reinvestigating the Product Structures of Enaminones with Malononitrile. A Novel Route to 6-Substituted-3-Oxo-2,3-Dihydropyridazine-4-Carboxylic Acids

Abstract: The reported structures of reaction products of enaminones with malononitrile in ethanolic piperidine are revised. A novel route to 2,3-dihydropyridazine-4-carboxylic acids 4a-c via reactions of 2-cyano-5-(dimethylamino)-5-arylpenta-2,4-dienamides 8a-c with nitrous acid or with benzenediazonium chloride is reported. Compounds 8a-c are converted to 1,2-dihydropyridine-3-carboxylic acid and 1,2-dihydropyridine-3-carbonitrile derivatives upon reflux in EtOH/ HCl and in AcOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 18 publications
(17 reference statements)
0
34
0
Order By: Relevance
“…In exploratory studies, we observed that chitosan promoted reactions of -enaminones 9a,b with malononitrile afford the same products obtained earlier from reactions of the same substrates in presence of piperidine [6,11]. Although it was proposed earlier that these products are conjugated amino nitriles, A, [12], we recently established on the basis of both Xray and 15 N NMR analysis that the products actually are the enedienes 12a,b (Scheme 2).…”
Section: Resultsmentioning
confidence: 57%
“…In exploratory studies, we observed that chitosan promoted reactions of -enaminones 9a,b with malononitrile afford the same products obtained earlier from reactions of the same substrates in presence of piperidine [6,11]. Although it was proposed earlier that these products are conjugated amino nitriles, A, [12], we recently established on the basis of both Xray and 15 N NMR analysis that the products actually are the enedienes 12a,b (Scheme 2).…”
Section: Resultsmentioning
confidence: 57%
“…Initially, AlOmran et al reported that 88 is the product of the reaction of these substances promoted by ethanolic sodium ethoxide, but suggested that 89 is produced when the reaction occurred in ethanolic piperidine (Scheme 21 and Table 16) [70]. Utilizing both 15 N NMR, HMBC NMR methods [71,72], and a subsequent X-ray crystal structural analysis, we demonstrated that the reaction product is really 90. It is quite strange that the results of our work were available in open-access journals at least a year before the report of similar results by Abdelrazek et al [68].…”
Section: Solvent-free Reactionsmentioning
confidence: 72%
“…However, in the process described above it appears that 17 follows a Dimroth-type rearrangement route to form the 2-pyridone ring in the polyhydroquinoline product 18. 22 Support for the assignment of the structure of 18 comes from the results of a NOE difference experiment that shows enhancements of resonances for methylene protons at δ 2.38 and 2.76 upon irradiation of the NH resonance at δ 12.29 and vice versa.…”
Section: Resultsmentioning
confidence: 99%